Like a Prayer? Applying Conflicts with Religious Dimensions Theory to the "Muezzin Law" Conflict - Yael Efron; Michelle LeBaron; Maged Senbel; Mohammed S. Wattad (Washington University Journal of Law & Policy, 2020)
What is the nature of the dispute around an Israeli law that proposes restricting how Muslim followers are called for prayer? And, why does the nature of this dispute hold any importance? LeBaron and Senbel have developed a theory differentiating conflicts with religious dimensions (CRDs) from other types of conflicts. The importance of this distinction stems from and highlights the unique role that religion plays in conflicts, which liberal, rational, and individualistic orientations to conflict management fail to address. This article offers a trial run of LeBaron and Senbel’s innovative theoretical framework. We apply CRD theory to conduct an analysis of a legislative attempt to amend an environmental law in Israel. The proposed amendment would limit the use of public address (PA) systems to amplify the Mouzins’ calls for prayer. Proposed limitations on this Islamic practice triggered a public outcry and a sharp societal dispute in Israel. The analysis in this article exposes the real conflict over the proposed amendment to be a CRD, rather than what it seemed on its face: an environmental regulation conflict. This article also contributes to further developing CRD theory. We elaborate on the combined effects of the conflict’s intensity, its duration, and the proximity of its subject to the core values of a religion. We suggest that identifying the unique amalgam of these aspects in a CRD is important to its effective management.
Keywords: conflict with religious dimensions; CRD; Muezzin Law; Muslim; Islam; prayer; religious; religion